Environmental Life Cycle Assessment of a Residential Building in Egypt: A Case Study. (2015) - Ali, Ahmed Abdel Monteleb M.; Negm, Abdelazim M.; Bady, Mahmoud F.; Ibrahim, Mona G.E.
Abstract: Residential buildings play prominent role in sustainable development and environmental impacts. Therefore, the aim of this paper is using the life cycle assessment (LCA) tool to assess the environmental impacts of the Egyptian typical residential building. SimaPro V8.1 was used in the analysis under ISO 14040 standards. Results show that the main contributor to all other environmental impacts are mainly those related to energy use in the operational/use stage contributing by (71.9%). On the other hand, the disposal scenarios provide positive environmental impacts by (-12.1%). Further possible measures to enhance the environmental impacts are mentioned in the paper conclusions.